Inadequate fluid intake can increase the risk of constipation among pregnant women - Dina Fitriana; Budi Prasetyo; Bangun Trapsila Purwaka (Majalah Obstetri dan Ginekologi, 2017)
Objectives: To analyze the association between the fiber and fluid consumption with constipation in pregnancy.Materials and Methods: An analytic cross-sectional study conducted at Jagir Public Health Center Surabaya, with the samples of healthy pregnant women aged between 20-35 years old (n=99). Respondents were asked to record the amount of daily fluid intake, defecation frequency, and type of faeces, everyday for 7 days, also made a food recall during 24 hours. The recom-mendation of adequate fluid intake in first trimester was 2180 ml/day and 2300 ml/day for second and third trimester. The value of adequate fiber consumption was 25-30 g/day. Constipation diagnosed by the frequency of defecation <2x/week, or based on Bristol Stool Form Scale included as type 1, type 2, or type 3.Results: Pregnant women whose adequate fluid intake was 40,4% and those with adequate fiber intake was 4.1%. The percentage of constipation among them was 29.5%. There was significant association between fluid intake and constipation (p: 0,000; RR:1,85). There was no significant association between fiber intake and constipation p:0,317 (p<0.05). There was also no significant association between parity, gestational age, and level of education with constipation (p<0.05).Conclusion: Inadequate maternal fluid intake can increase the risk of constipation by 1.85 folds, and the adequate fluid intake may prevent constipation during pregnancy.